Modelling the combined effects of salt, sorbic acid and nisin on the probability of growth of Clostridium sporogenes in a controlled environment (nutrient broth). (April 2016) - Khanipour, Elham; Flint, Steve H.; McCarthy, Owen J.; Golding, Matt; Palmer, Jon; Ratkowsky, David A.; Ross, Tom; Tamplin, Mark
Abstract: The safe preservation of new generation foods (high moisture, low salt, high pH and shelf stable under ambient conditions) is microbiologically challenging. The growth of Clostridium botulinum in low acid foods is a hazard for consumers. In this study the combined effect of salt (sodium chloride) (0–4% w/v), potassium sorbate (0–4% w/v) and nisin (0–300 ppm) at two different pHs (5.5 and 7) on the probability of growth of Clostridium sporogenes spores, as a non-toxigenic surrogate of C. botulinum, was evaluated in nutrient broth. Nutrient broth was used as it can easily and accurately be adjusted and controlled in terms of composition, and allows more rapid growth than is observed in food. The aims of this study were to develop probability of growth models in which the logit is expressed as a function of the concentrations of the selected preservatives. The developed models fit the data adequately. The c -values models were close to 1, indicating good predictive power. This indicates the performance of models would be satisfactory. The results of this study indicated that salt, potassium sorbate and nisin had significant inhibitory effects on the growth of C. sporogenes in high moisture (>95%) and high pH conditions (pH > 4.5). Combinations of the selected preservatives were more effective than any of them individually. The inhibitory effects of all three preservatives in the current study were pH dependent. Less stringent combinations of preservative concentrations were required experimentally to stop growth at pH 5.5 compared with pH 7. Highlights: Probability models can quantify preservative concentration. Combinations of salt, nisin and sorbate were more effective on Clostridium sporogenes . 4% salt could not prevent growth of C. sporogenes in absence of sorbate and nisin.